Maladaptive autonomic regulation in PTSD accelerates physiological aging - Williamson, John B.; Porges, Eric C.; Lamb, Damon G.; Porges, Stephen W. (Frontiers in Psychology, 2015)
A core manifestation of posttraumatic stress disorder is a disconnection between physiological state and psychological and behavior processes necessary to adequately respond to environmental demands. Patients with PTSD experience oscillations in autonomic states that support either fight and flight behaviors or withdrawal, immobilization, and dissociation without an intervening “calm” state that would provide opportunities for positive social interactions. This defensive autonomic disposition is adaptive in dangerous and life threatening situations, but in the context of every-day life may lead to significant psychosocial distress and deteriorating social relationships. The perpetuation of these maladaptive autonomic responses, may contribute to the development of comorbid mental health issues such as depression, loneliness, and hostility that further modify the nature of cardiovascular behavior in the context of internal and external stressors. Over time, changes in autonomic, endocrine, and immune function contribute to deteriorating health, which is potently expressed in brain dysfunction and cardiovascular health. In this theoretical review paper, we review the literature on the chronic health effects of post-traumatic stress disorder. We discuss the brain networks underlying post-traumatic stress disorder in the context of autonomic efferent and afferent contributions and how disruption of these networks leads to poor health outcomes. Finally, we discuss treatments based on our theoretical model of posttraumatic stress disorder.